PENGARUH PROMOSI DAN WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG MELALUI DESTINATION IMAGE (Studi Kasus pada Wisatawan Grand Maerakaca Semarang) - Rendi Giyanova Widyanto; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2019)
Tourism is one of the potential business sectors because the community's need to travel continues to increase. Grand Maerakaca is a type of artificial tourism that has the concept of culture and education about the culture of Central Java. Grand Maerakaca is one of the leading tourist destinations in Semarang, but because there are still problems in the Grand Maerakaca, tourists are hesitant to visit. This type of research is explanatory research, using a questionnaire as a method of data collection. The research method used is the Non Probability Sampling technique with Purposive Sampling and Accidental Sampling methods. Samples collected as many as 100 respondents of Grand Maerakaca Semarang tourists were selected based on consideration. The study uses a Partial Least Square analysis technique, which is estimated with the WarpPLS 6.0 program. The results of the analysis by WarpPLS explain that the test results of the direct effect on the research model are the influence of Promotion on Visiting Decisions showing positive and significant results, the influence of Word of Mouth on Visiting Decisions shows positive and significant results, the effect of Promotion on Destination Image shows positive and significant results, Word of Mouth towards Destination Image shows positive and significant results, and the effect of Destination Image on Visiting Decisions shows positive and significant results. Test the indirect effect on the research model that is the effect of Promotion of Visiting Decisions through Destination Image shows positive and significant results, the effect of Word of Mouth on Visiting Decisions through Destination Image shows positive and significant results. Researchers give advice to the Grand Maerakaca based on the lowest recapitulation value given by respondents to the assessment indicators, namely adding detailed information on their social media, stimulating positive word of mouth, considering making iconic entrance access, and continuing to increase the quantity and quality of promotions on social media. which is close to potential tourists.